PÅVIRKER KULTUREN SMERTEN? Om voldsomme udbrud og diskrete rynker i panden - Tørring, Marie Louise (Tidsskriftet Antropologi, 2008)
In this article, the author urges anthropologists to stop ignoring culture’s presence in social life and to take a more contextual approach to pain and culture in order to challenge the emergent cultural essentialism in health care literature. The study is founded on six months of ethnographic fieldwork conducted at postoperative pain units and surgical wards in Danish and Italian hospitals in 2003 and 2004. The author employs Bruno Latour’s concepts to analyse the dynamic process of acute pain management and illustrates how culture and pain are merged in the clinical setting. Scientific paradigms, drugs, self-reporting scales, human resources, monitors, guidelines, habits, and cultural beliefs all shape the way people respond to pain. Thus, actor-network theory proves itself as an alternative, useful tool for understanding the way cultural stereotypes equally affect pain behaviour, pain treatment and the pain experiences.